Angle Quadrisector

Geometry Level 4

In triangle A B C ABC , the perpendicular, angle bisector and median of vertex C C split angle A C B ACB into 4 equal parts. What is the measure (in degrees) of A C B \angle ACB ?


The answer is 90.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Let the four equal parts be A C D \angle ACD , D C E \angle DCE , E C F \angle ECF , F C B \angle FCB , where ADEFB is a straight line. It is obvious that C E CE is the angle bisector. WLOG let A C > C B AC>CB . Then C F CF is the perpendicular and C D CD is the median. Let A C D = α \angle ACD=\alpha , E F = F B = b EF=FB=b , and A D = D B = c AD=DB=c . Then tan α = b \tan \alpha =b , tan 2 α = c b \tan 2\alpha=c-b , tan 3 α = 2 c b \tan 3\alpha=2c-b . Thus, tan 3 α = 2 c b = 2 ( c b ) + b = 2 t a n 2 α + tan α \tan 3 \alpha = 2c-b = 2(c-b)+b = 2 tan 2\alpha + \tan \alpha . Using the double and triple angle formula for tangent, we obtain 3 b c 3 1 3 b 2 = 4 b 1 b 2 + b \frac {3b-c^3}{1-3b^2} = \frac {4b}{1-b^2}+b . Clearing denominators, we obtain b ( b 4 6 b 2 + 1 ) = 0 b(b^4 - 6b^2 + 1 )=0 . If b = 0 b = 0 , then tan α = 0 α = 0 \tan \alpha = 0 \Rightarrow \alpha = 0 , which makes it a degenerate triangle. Thus, b 4 6 b 2 + 1 = 0 b 4 2 b 2 + 1 = 4 b 2 2 b 1 b 2 = ± 1 b^4-6b^2 + 1 = 0 \Rightarrow b^4 - 2 b^2 + 1 = 4 b^2 \Rightarrow \frac {2b}{1-b^2} = \pm 1 . Notice that this is tan 2 α = ± 1 \tan 2 \alpha = \pm 1 , hence we either have 2 α = 4 5 2 \alpha = 45^\circ or 13 5 135 ^\circ (we reject the latter). Hence, 4 α = 9 0 4 \alpha = 90^\circ .

Calvin Lin Staff
May 13, 2014

Let D , E D, E and F F be the intersection of A B AB with the perpendicular, the angle bisector and the median of C C , respectively. Since the angle bisector splits the angle into 2 equal parts, we may assume that the perpendicular is closer to A A (else flip the vertices A , B A, B ), so points A , D , E , F A, D, E, F and B B lie in order.

Since A D C = C D E = 9 0 \angle ADC = \angle CDE = 90^\circ and A C D = E C D \angle ACD = \angle ECD , we have that triangles C A D CAD and C E D CED are congruent. Thus C E = A C CE = AC and E D = D A ED=DA . By the angle bisector theorem, we have C A C B = A E E B \frac {CA}{CB} = \frac {AE}{EB} , C B C E = B F F E \frac {CB}{CE} = \frac {BF}{FE} and C F C D = F E E D \frac {CF}{CD}=\frac {FE}{ED} .

Let A D = x AD = x and B F = y BF = y , so y = B F = A F > A E = 2 x y = BF = AF > AE = 2x and F E = y 2 x FE = y-2x . Then 2 y 2 x 2 x = B E E A = B C C A = B C C E = B F F E = y y 2 x \frac {2y-2x}{2x} = \frac {BE}{EA} = \frac {BC}{CA} = \frac {BC}{CE} = \frac {BF}{FE} = \frac {y}{y-2x} . This gives y 2 4 x y + 2 x 2 = 0 y^2 -4xy + 2x^2 =0 . Taking the equation as a quadratic in y y and using the quadratic formula, we have y = ( 2 + 2 ) x y = (2 + \sqrt{2} )x (ignore other root since y > 2 x y > 2x .)

Since C D F = 9 0 \angle CDF = 90^\circ , we have C F D = sin 1 ( C D C F ) \angle CFD = \sin^{-1} \left(\frac {CD}{CF}\right) and C D C F = D E E F = x y 2 x = 1 2 \frac{CD}{CF} = \frac {DE}{EF} = \frac {x}{y-2x} = \frac {1}{\sqrt{2} } . So C F D = sin 1 ( 1 2 ) = 4 5 \angle CFD = \sin^{-1} \left( \frac{1}{\sqrt{2}}\right) = 45^\circ which implies that F C D = 18 0 9 0 4 5 = 4 5 \angle FCD = 180^\circ - 90^\circ - 45^\circ = 45^\circ and thus we have A C B = 2 × 4 5 = 9 0 \angle ACB = 2\times 45^\circ = 90^\circ .

Wing Tang
Aug 21, 2018

Let D , E D,E and F F be the points on A B AB such that C D CD , C E CE and C F CF are respectively the altitude, angle bisector and median of the vertex C C . WLOG, let A C < B C AC < BC . Since they split A C B \angle ACB into 4 equal parts, let A C D = D C E = E C F = F C B = α \angle ACD = \angle DCE = \angle ECF = \angle FCB = \alpha .

In the two right-angled triangles A C D ACD and C D B CDB , A C D = α \angle ACD = \alpha and B C D = 3 α \angle BCD = 3\alpha and, therefore, their complementary angles in the respective triangles are A = 9 0 α \angle A = 90^\circ - \alpha and B = 9 0 3 α \angle B = 90^\circ - 3\alpha .

Applying the law of sines to A C B \triangle ACB , we have

\displaystyle \begin{aligned} \frac{AC}{CB} &= \frac{\sin B}{\sin A}\\ & \\ &= \frac{\sin (90^\circ - \alpha)}{\sin (90^\circ - 3\alpha)}\\ & \\ &= \frac{\cos \alpha}{\cos 3\alpha}. \tag{0} \end{aligned}

On the other hand, we can apply the law of sines to A C F \triangle ACF and C F B \triangle CFB to get another result for A C C B \displaystyle \frac{AC}{CB} .

\displaystyle \frac{AC}{\sin \angle CFA} = \frac{AF}{\sin 3\alpha}\tag{1}

and

\displaystyle \frac{CB}{\sin\angle CFB} = \frac{AF}{\sin 3\alpha}\tag{2}

respectively. Here, we note C F A = 18 0 C F B \angle CFA = 180^\circ - \angle CFB and sin C F A = sin ( 18 0 C F B ) = sin C F B \sin \angle CFA = \sin (180^\circ - \angle CFB) = \sin \angle CFB . So, dividing (1) through (2) yields

\displaystyle \frac{AC}{CB} = \frac{\sin 3 \alpha}{\sin \alpha}. \tag{3}

Equating (0) and (3) yields

sin 3 α sin α = cos α cos 3 α \displaystyle \frac{\sin 3 \alpha}{\sin \alpha} = \frac{\cos \alpha}{\cos 3\alpha}

which implies sin 3 α cos 3 α = sin α cos α \displaystyle \sin 3\alpha \cos 3 \alpha = \sin \alpha \cos \alpha . Using sin 2 θ = 2 cos θ sin θ \sin 2 \theta = 2 \cos \theta \sin \theta , it is equivalent to sin 6 α = sin 2 α \displaystyle \sin 6\alpha = \sin 2 \alpha . Since 0 < 4 α < 18 0 0<4\alpha < 180^\circ , we see that 6 α < 36 0 6\alpha < 360^\circ . So we have either 6 α = 2 α 6 \alpha = 2 \alpha or 6 α = 18 0 2 α 6 \alpha = 180^\circ - 2\alpha . The former must be rejected for α \alpha cannot be zero, and the latter gives α = 22. 5 \alpha = 22.5^\circ which is consistent with 4 α < 18 0 4\alpha < 180^\circ . So, A C B = 4 α = 9 0 \angle ACB = 4\alpha = 90^\circ .

Kumar Ashutosh
May 20, 2014

Here, let CD, CE and CF be the perpendicular, angle bisector and median respectively. Now the angle is split into 4 equal parts. So angle bisector must be between perpendicular and median. Hence, CE is between CD and CF. Now let the measure of angle ACB be 4Y. So angle of each division = Y. Now, we know that a median divides a triangle into two triangles of equal area. Hence, ar.(CFB) = ar.(CAF) where ar.() denotes area of figure ar.(CFB) = ar.(CAD) + ar.(CDE) + ar.(CEF) Applying sine rule regarding area of triangle ½ BC *CF sinY = ½ CF CE sinY + ½ CE CD sinY +1/2 CD CA sinY implies BC CF = CF CE+CE CD+CD CA ...........(1) Now, CD is the perpendicular. So, CDE, CDF, CAD and CDB are right triangles and applying trigonometry, CE = CD secY, CF = CD sec(2Y), CB = CD sec(3Y), CA= CD secY Putting these values in equation ....(1) we get {CD sec(3Y)} * {CD sec(2Y)} = {CD sec(2Y)} {CD sec(Y)} + {CD} {CD secY} + {CD} {CD sec(Y)} implies sec(3Y)* sec(2Y) = sec(Y)* sec(2Y) + 2 sec(Y) Solving this equation for Y we get {sin(Y)}^2 = (2+ (2)^0.5)/4 or {sin(Y)}^2 = (2-(2)^0.5)/4 \Rightarrow Y = 67.5 or Y = 22.5 where angles are in degrees But if Y = 67.5 then 4Y = 270 , So this case is not possible in a triangle Therefore Y = 22.5 And hence angle ACB = 4Y = 4 22.5 = 90

Ramiel To-ong
Jun 8, 2015

that's 22.5 x 4 = 90

How do you know that one part must be 22.5 degrees?

Calvin Lin Staff - 6 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...